Observatório do esporte: uma visão crítica da mídia esportiva na rádio Unesp FM - Pavini, Tiago Pátaro [UNESP] (2015)
The "Observatory of Sports" is a radio program that since 2010 is aired by Radio UNESP FM in the early hours of saturday (at midnight) with reruns on saturdays at 11 am, where through the infotainment strategy are discussed various issues of the sporting daily with further analysis, especially the sports media. With an approach of multimethodological evaluation, the project seeks to articulate extension and professionalism in journalism and sports broadcasting for the teaching and learning of students and fellows of undergraduate and postgraduate of FAAC - School of Architecture, Arts and Communication at UNESP, Bauru, occur in current mode, dynamic and connected to empirical research in communication.